Effect of zirconia nanoparticles modified by silane coupling agent on some properties of epoxy coating - Dao Phi Hung,; Nguyen Thuy Chinh,; Nguyen Anh Hiep,; Nguyen Xuan Thai,; Ly Thi Ngoc Lien,; Dao Huu Toan,; Hoang Thi Huong Giang,; Thai Hoang, (Vietnam Journal of Science and Technology, 2022)
Effect of zirconia nanoparticles (zirconia NPs/ZrO2 NPs) modified by 3 wt.% (glycidyloxypropyl) triethoxysilane – GPTES (m-ZrO2 NPs) on some properties of epoxy coating such as mechanical properties, thermal stability and anti-corrosion performance was investigated. The obtained results indicated that the addition of zirconia nanoparticles to epoxy coating could enhance the properties of this coating. The addition of 2 wt.% of pure ZrO2 NPs (u-ZrO2 NPs) to the epoxy matrix could increase the mechanical properties (hardness and adhesion to the steel substrate) by approximately 10 %, the onset temperature of thermal degradation of the epoxy/u-ZrO2 NPs coating was 4.4 oC higher, and the anti-corrosion performance of epoxy coating was improved in comparison with the neat epoxy coating. Organically modified ZrO2 NPs had higher improvement for epoxy coating’s properties than pure ZrO2 NPs. The epoxy coating filled with m-ZrO2 NPs had 19.7 % higher in relative hardness, 88.73 % more in adhesion to steel substrate, 25.6 oC higher in the onset temperature of thermal degradation, and higher anti-corrosion performance in comparison with the epoxy coating filled with 2 wt.% of pure zirconia nanoparticles. The cross-section FESEM images of the epoxy/m-ZrO2 NPs coating showed that m-ZrO2 NPs could regularly disperse in epoxy polymer matrix while unmodified zirconia nanoparticles (u-ZrO2 NPs) were agglomerated to big cluster in the epoxy coating. This was the reason for the high performance of the epoxy coating filled with zirconia NPs modified by GPTES.